Night Zookeeper: The Penguins of Igloo City - Davidson, Joshua (Oxford Oxford University Press, 2019)
When Will accidentally creates a mysterious portal during a trip to the zoo, he's transported into the world of the Night Zoo, and thrust into an incredible adventure. Joined by his friends, Sam and Riya, Will journeys through a new portal and arrives within the high walls of Igloo City. It is a strange place where the animals follow strict rules put in place by their leader, Circles the owl. Circles is determined to stamp out any rule breakers and wants Will to track down a group of rebels, but is it the right thing to do? The safety of Igloo City depends on Will choosing the right side - will he follow Circles' orders, or break free from her rules and join the rebels?